Inverting Cauchy

Algebra Level 5

For any positive integer n n , the n × n n \times n matrix X ( n ) X(n) has components X ( n ) i j = 1 i 2 + j 2 1 i , j n X(n)_{ij} \; = \; \frac{1}{i^2 + j^2} \hspace{2cm} 1 \le i,j \le n Let σ n \sigma_n be the sum of the n 2 n^2 components of the inverse matrix X ( n ) 1 X(n)^{-1} , so that σ n = i , j = 1 n X ( n ) i j 1 \sigma_n \; = \; \sum_{i,j=1}^n X(n)^{-1}_{ij} It can be shown that n = 1 1 σ n = a b ln c \sum_{n=1}^\infty \frac{1}{\sigma_n} \; = \; a - b\ln c where a , b , c a,b,c are positive integers, and c c is prime. What is the value of a + b + c a + b + c ?


The answer is 23.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jul 7, 2020

The matrix X ( n ) X(n) is a special case of what is called a Cauchy matrix, namely one of the form H i j = 1 a i b j 1 i , j n H_{ij} \; = \; \frac{1}{a_i - b_j} \hspace{2cm} 1 \le i,j \le n where a 1 , a 2 , , a n , b 1 , b 2 , , b n a_1,a_2,\ldots,a_n,b_1,b_2,\ldots,b_n are all distinct. It is possible to find an explicit formula for the inverse of H H . To do this, define the interpolation polynomials A ( X ) j = 1 n ( X a j ) B ( X ) j = 1 n ( X b j ) A i ( X ) 1 A ( a i ) j i ( X a j ) B i ( X ) 1 B ( b i ) j i ( X b j ) 1 i n \begin{array}{rclcrclcl} A(X) &\equiv& \displaystyle \prod_{j=1}^n (X - a_j) &\hspace{1cm}& B(X) &\equiv& \displaystyle \prod_{j=1}^n (X - b_j) \\[2ex] A_i(X) &\equiv& \displaystyle \frac{1}{A'(a_i)}\prod_{j \neq i}(X - a_j) && B_i(X) &\equiv& \displaystyle \frac{1}{B'(b_i)}\prod_{j \neq i}(X - b_j) &\hspace{2cm}& 1 \le i \le n \end{array} so that A i ( a j ) = B i ( b j ) = δ i j A_i(a_j) = B_i(b_j) = \delta_{ij} for 1 i , j n 1 \le i,j \le n and Q ( X ) i = 1 n Q ( a i ) A i ( X ) i = 1 n Q ( b i ) B i ( X ) Q(X) \; \equiv \; \sum_{i=1}^n Q(a_i)A_i(X) \; \equiv \; \sum_{i=1}^n Q(b_i)B_i(X) for any polynomial Q ( X ) Q(X) of degree n 1 n-1 or less.

Define the n × n n \times n matrix G G by G i j = A ( b i ) B i ( a j ) A ( a j ) 1 i , j n G_{ij} \; = \; -\frac{A(b_i) B_i(a_j)}{A'(a_j)} \hspace{2cm} 1 \le i,j \le n Then, for 1 i n 1 \le i \le n , A ( b i ) B i ( X ) j = 1 n A ( b i ) B i ( a j ) A j ( X ) = j = 1 n G i j k j ( X a k ) A ( b i ) B i ( X ) A ( X ) j = 1 n G i j X a j j = 1 n G i j a j X \begin{aligned} -A(b_i)B_i(X) & \equiv \; -\sum_{j=1}^n A(b_i)B_i(a_j)A_j(X) \; = \; \sum_{j=1}^n G_{ij}\prod_{k \neq j}(X - a_k) \\ \frac{A(b_i)B_i(X)}{A(X)} & \equiv \; -\sum_{j=1}^n \frac{G_{ij}}{X - a_j} \; \equiv \; \sum_{j=1}^n \frac{G_{ij}}{a_j - X} \end{aligned} so that j = 1 n G i j H j k = j = 1 n G i j a j b k = A ( b i ) B i ( b k ) A ( b k ) = δ i k 1 i , k n \sum_{j=1}^n G_{ij}H_{jk} \; = \; \sum_{j=1}^n \frac{G_{ij}}{a_j - b_k} \; = \; \frac{A(b_i)B_i(b_k)}{A(b_k)} \; = \; \delta_{ik} \hspace{2cm} 1 \le i,k \le n Thus G = H 1 G = H^{-1} ; moreover H i j 1 = G i j = B i ( a j ) A ( a j ) ( b i a j ) k j ( b i a k ) = ( a j b i ) A j ( b i ) B i ( a j ) 1 i , j n H^{-1}_{ij} \; = \; G_{ij} \; = \; -\frac{B_i(a_j)}{A'(a_j)}(b_i-a_j)\prod_{k \neq j}(b_i - a_k) \; = \; (a_j - b_i)A_j(b_i)B_i(a_j) \hspace{2cm} 1 \le i,j \le n We also note that i = 1 n A j ( b i ) B i ( a j ) = A j ( a j ) = 1 j = 1 n A j ( b i ) B i ( a j ) = B i ( b i ) = 1 \sum_{i=1}^n A_j(b_i)B_i(a_j) \; = \; A_j(a_j) \; = \; 1 \hspace{2cm} \sum_{j=1}^n A_j(b_i)B_i(a_j) \; = \; B_i(b_i) \; = \; 1 and hence i , j = 1 n H i j 1 = j = 1 n a j ( i = 1 n A j ( b i ) B i ( a j ) ) i = 1 n b i ( j = 1 n A j ( b i ) B i ( a j ) ) = i = 1 n ( a i b i ) \sum_{i,j=1}^n H^{-1}_{ij} \; = \; \sum_{j=1}^n a_j\left(\sum_{i=1}^n A_j(b_i)B_i(a_j)\right) - \sum_{i=1}^n b_i\left(\sum_{j=1}^n A_j(b_i)B_i(a_j)\right) \; = \; \sum_{i=1}^n(a_i - b_i)

In the particular case of X ( n ) X(n) , we have a i = i 2 a_i = i^2 and b j = j 2 b_j = -j^2 for 1 i , j n 1 \le i,j \le n , and hence σ n = i = 1 n 2 i 2 = 1 3 n ( n + 1 ) ( 2 n + 1 ) n 1 \sigma_n \; = \; \sum_{i=1}^n 2i^2 \; = \; \tfrac13n(n+1)(2n+1) \hspace{2cm} n \ge 1 Thus n = 1 N 1 σ n = 3 n = 1 N 1 n ( n + 1 ) ( 2 n + 1 ) = 3 n = 1 N ( 1 n + 1 n + 1 4 2 n + 1 ) = 3 [ 3 + 4 n = 1 N 1 n 4 n = 1 2 N 1 n + 1 N + 1 4 2 N + 1 ] = 3 [ 3 + 4 S N 4 S 2 N 4 ln 2 + 1 N + 1 4 2 N + 1 ] \begin{aligned} \sum_{n=1}^N \frac{1}{\sigma_n} & = \; 3\sum_{n=1}^N \frac{1}{n(n+1)(2n+1)} \; = \; 3\sum_{n=1}^N \left(\frac{1}{n} + \frac{1}{n+1} - \frac{4}{2n+1}\right) \\ & = \; 3\left[3 + 4\sum_{n=1}^N \frac{1}{n} - 4\sum_{n=1}^{2N}\frac{1}{n} + \frac{1}{N+1} - \frac{4}{2N+1}\right] \\ & = \; 3\left[3 + 4S_N - 4S_{2N} - 4\ln2 + \frac{1}{N+1} - \frac{4}{2N+1}\right] \end{aligned} where S N = n = 1 N 1 n ln N S_N \; = \; \sum_{n=1}^N \frac{1}{n} - \ln N is well-known to converge to the Euler-Mascheroni constant γ \gamma as N N \to \infty . Thus we deduce that n = 1 1 σ n = 3 ( 3 4 ln 2 ) = 9 12 ln 2 \sum_{n=1}^\infty \frac{1}{\sigma_n} \; = \; 3(3 -4\ln2) \; = \; 9 - 12\ln2 making the answer 9 + 12 + 2 = 23 9 +12 + 2 = \boxed{23} .

@Mark Hennings sir can you please post the solution of my this Problem
Thanks in advance.

A Former Brilliant Member - 11 months, 1 week ago

is the main idea in this problem related to polynomial interpolation. this is not an easy problem. it requires good amount of effort.

Srikanth Tupurani - 11 months, 1 week ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...